Necrotising fasciitis secondary to perforated rectal adenocarcinoma presenting as a thigh swelling - Evans, William David George (BMJ Case Rep, 2015)
A 62-year-old man was admitted to the medical admissions ward with right thigh pain presumed to be a deep vein thrombosis (DVT). Subsequent duplex ultrasonography excluded a DVT but noted the presence of a significant amount of subcutaneous gas. A plain film radiograph was performed with the same finding raising the possibility of necrotising fasciitis (NF). Only at this point was digital rectal examination performed revealing a large rectal mass oozing pus and blood. CT imaging showed thickening of the rectum consistent with a tumour with gas and fluid in the perirectal space extending to the anterolateral right femur. Despite aggressive debridement and treatment, the patient deteriorated and died 6 weeks later. This case should serve as a reminder to consider digital rectal examination and the occurrence of a rectal perforation in all patients who present with suspicious thigh swellings.